The effect of tinea versicolor on thiol/disulphide homeostasis - Kilinc, Fadime (Postepy Dermatol Alergol, 2018)
INTRODUCTION: Tinea versicolor is a superficial fungal infection caused by Malassezia spp. Malassezia spp. is a member of the normal human skin flora. It becomes a pathogen by transforming from the yeast form to the mycelium form. The oxidant/antioxidant homeostasis may be responsible for this. Thiol/disulphide homeostasis is a new marker indicating oxidative stress. This homeostasis is affected in many illnesses. AIM: To investigate the thiol/disulphide homeostasis in patients with tinea versicolor. MATERIAL AND METHODS: Forty-two patients with tinea versicolor (median age: 36 years, min.–max.: 19–58) and 36 healthy controls (median age: 32 years, min.–max.: 18–60) were included in the trial. The levels of native thiol, disulphide, and total thiol were measured by an automated method in the patient and control groups. Disulphide/total thiol, disulphide/native thiol and native thiol/total thiol rates were calculated as percentage. RESULTS: For the patient group and the control group, the native thiol levels were found to be 464.32 ±51.48 mmol/l and 465.18 ±51.32 mmol/l, disulphide levels – 19.80 ±7.08 mmol/l and 21.27 ±8.90 mmol/l, total thiol levels – 503.92 ±53.65 mmol/l and 508.07 ±56.59 mmol/l, respectively. No statistical difference was detected between the two groups. CONCLUSIONS: Thiol/disulphide homeostasis was not affected in tinea versicolor. According to our findings, oxidative stress seems to have no role in the pathogenesis of tinea versicolor.